1986
DOI: 10.2135/cropsci1986.0011183x002600030034x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Reproductive Abortion in Soybean1

Abstract: The abortion of reproductive plant parts is an important, but not well understood, part of the yield production process in many crop plants. The objective of this research was to characterize the effects of growth stage and timing on the abortion process of soybean [Glycine max (L.) Merr.] flowers exhibiting variation in abortion. Soybean plants were grown in a greenhouse (cv. McCall) and for 3 yrs in the field (cv. Kent). The soil types were a Donerail silt loam (Typic Arguidofl), Maury silt loam (Typic Paleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 0 publications
4
55
0
4
Order By: Relevance
“…2, T able 2) . Hei tholt et al ( 1986) reported tha t the accu mula tion of dry matter in the pod was slower in Kent (M aturity group: [V) than in M cCall (M atu rity group: 00). Umezaki ( 1991) recorded a great variation in the timing of pod lo rm ation among cultivars within the same maturity gro up.…”
Section: Short Photoperiod Treatmentmentioning
confidence: 99%
“…2, T able 2) . Hei tholt et al ( 1986) reported tha t the accu mula tion of dry matter in the pod was slower in Kent (M aturity group: [V) than in M cCall (M atu rity group: 00). Umezaki ( 1991) recorded a great variation in the timing of pod lo rm ation among cultivars within the same maturity gro up.…”
Section: Short Photoperiod Treatmentmentioning
confidence: 99%
“…The node location of a flower in soybean main axis determines, in part, when it develops. This time of a flower developing is a critical factor in determining it survival or abscission, because at individual node, the abortion of early developing flowers always had lower than those developing later (Brun and Betts, 1984;Heitholt et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…By reducing this abortion, we might be able to increase pod and seed numbers, thereby increasing the yield (Kokubun, 2004). Many previous studies have focused on two possible factors that might be involved in regulating the abortion; availability of photoassimilate or nutrients (Brevedan et al, 1978;Antos and Wiebold, 1984;Brun and Betts, 1984;Heitholt, 1986aHeitholt, , 1986b and quantity of certain hormones (Huff and Dybing, 1980;Heindl et al, 1982;Spollen et al, 1986aSpollen et al, , 1986bCarlson et al, 1987;Yarrow et al, 1988;Kokubun and Honda, 2000).…”
mentioning
confidence: 99%